A Protective role of sulforaphane on alveolar epithelial cells exposed to cigarette smoke extract. (1st November 2013) - Jiao, Zongxian; Zhang, Qiangnu; Chang, Jiachen; Nie, Dengmei; Li, Min; Zhu, Yanfang; Wang, Chenyu; Wang, Yong; Liu, Feng
ABSTRACT: Background : Sulforaphane (SFN) is an excellent antioxidant agent, few of the studies focus on the possible protective role of SFN from cigarette smoke-induced injury on alveolar epithelial cells. Objectives : the aim of the study is to observe the possible protective role of SFN, as well as the function of insulin-like growth factor binding protein-3 (IGFBP-3) in the process. Methods : MTT assay was used to evaluate cell viability after cigarette smoke extract (CSE) and/or SFN exposure, cell cycle was analyzed using flow cytometry, intracellular reactive oxygen species (ROS) level was detected by staining with fluorescent indicator 2′, 7′-dichlorofluorescin diacetate (DCFH-DA), finally both real-time quantitative RT-PCR and western blot were employed to observe mRNA and protein levels of IGFBP-3. Results : SFN could restore the viability of A549 cells, attenuate G1 block of the cell cycle, and significantly reduce the proportion of sub-G1 cells; at the same time, CSE-induced accumulation of intracellular ROS was decreased by SFN. Interestingly, high expression of IGFBP-3 was found at both transcriptional and translational levels, however by pre-incubation with SFN, the expression of IGFBP-3 was not stimulated by CSE exposure. Conclusions : SFN can antagonize CSE-induced growth arrest of alveolar epithelial cells and IGFBP-3 probably plays an important role in the process.